Compendium of Good Practices in Implementing the WTO Trade Facilitation Agreement: Experiences from Developing and Least Developed Countries - United Nations Conference on Trade; Development (United Nations, 2022)
The Compendium is intended to inspire policymakers to implement various measures of the World Trade Organization Trade Facilitation Agreement (TFA), drawing on experiences that have been tried and tested elsewhere. These examples of good practices not only present the implementation activities but also the challenges faced in their development and execution, as well as the key factors for a successful outcome. The intention is to help transfer the experience and lessons learned so that others can avoid common pitfalls and achieve results more efficiently.